SOSIAL EKONOMI DAN KONDISI KERJA PEREMPUAN PEDAGANG MAKANAN KAKI LIMA PADA MASA PANDEMI COVID-19 DI JAKARTA - Dionisius Yusuf (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
This study discusses the issues of women migrants in the street food sector in Indonesia, especially in Jakarta. This paper tries to describe the demographic and working conditions of migrant women street vendors in the city of Jakarta. This study used a sample of 100 women street vendors in the city of Jakarta with various methods of data collection. The cities were specifically selected due to rapidly increasing numbers of street food vendors. The selection of respondents used purposive sampling technique. The researcher's observations were used to collect data. Quantitative data were analyzed using percentages, bivariate analysis, Pearson analysis, and Chi-square. The results showed that among women street vendors, the age group of 20 to 50 years was the dominant group in Jakarta. Most of the vendors were poorly educated. The majority of the vendors are of Javanese ethnicity and come from Central Java and East Java. The majority of traders were married with 2-3 children. Furthermore, the daily life of women street vendors during the Covid-19 pandemic was marked by worse working conditions than before the Covid-19 pandemic, where 96% of the vendors said their income had decreased because of the Covid-19 pandemic. The research also shows that the average net income of women street food vendors has decreased by more than 30% during the pandemic Covid-19.